Global Production Networks and Regional Integration - Sven W. Arndt (Claremont McKenna College, Department of Economics, 2003)
Section I examines the implications of production sharing in the context of preferential trade liberalization. Of particular interest is the case in which a free trade area which is clearly trade-diverting under traditional circumstances, becomes trade-creating with joint production. Trade in components has important implications for the interaction between exchange rates and the trade balance. Trade tends to become less sensitive to exchange-rate changes and trade-balance accounting needs to distinguish between the value of total trade and trade in value-added. When production sharing takes place between advanced and emerging economies, foreign investment flows occur and capacity accumulation typically precedes the onset of joint production. This introduces cycles into the behavior of the real exchange rate and the current account. The real rate appreciates and the current balance deteriorates during the investment phase of the process, followed by real depreciation and current account improvement. The rest of the chapter is organized as follows. Section II lays out the basic argument in a standard general-equilibrium framework, while Section III examines key welfare effects of joint production in a partial-equilibrium framework. Section IV studies the effect of production sharing on the exchange-rate sensitivity of trade and discusses alternative measurements of the balance of trade. Section V deals with the real-exchange-rate effects of an investment cycle associated with the implementation of joint production. Section VI considers exchange-rate regime choice. Section VII concludes.
Keywords: 330; Internationale Arbeitsteilung; Business Network; Handelsregionalismus; Freihandelszone; Aussenhandelspräferenz; Aussenhandelseffekt